TRANSFORMATION OF FUNCTION, ADAPTATION, AND THE IMPACT OF MODERNIZATION ON CULTURAL VALUES IN THE KECAK DANCE PERFORMANCE AT MELASTI BEACH, BALI - RADITKA RAFI PERMANA; MIRWANSYAH; DWI NANDA AZZA REGINA RAHMA MEIDITYA PUTRI SANTOSO; LINDA TRIANA RAHMAWATI; MAYANG ARMADANI; NABILA RAMBI SHAKILA; SUGIANTORO (Innovare Journal of Social Sciences, 2025)
This research examines the transformation of functions, adaptation, and the impact of modernization on cultural values in the Kecak Dance performance at Melasti Beach, Bali. This research uses a phenomenological qualitative approach with data collection techniques through observation, in-depth interviews with local artists, cultural figures, and audiences, performance documentation, and we also collect data through questionnaires. This research aims to understand the shift in the function of Kecak Dance from a sacred religious ritual to a tourism performance, as well as how the local community adapts to cultural changes in the era of globalization. The research results show that although modernization and commercialization have introduced entertainment elements and technical changes in the performance, the core story, symbolic meaning, and sacred value of the Kecak Dance have been maintained within the context of tradition and religious ceremonies. Modernization is also viewed positively by the local community because it provides economic benefits, opens job opportunities, and introduces Balinese cultural identity to the international stage. Local artists and cultural figures continue to maintain a balance between innovation and cultural preservation through education, sacred performances, and active collaboration with the government. This research provides a new perspective on cultural resilience in tourism areas and offers recommendations for the sustainable development of cultural tourism in Bali.